Intratumoral heterogeneity in programmed death‐ligand 1 immunoreactivity is associated with variation in non‐small cell lung carcinoma histotype. Issue 3 (23rd December 2019) - Naso, Julia R; Wang, Gang; Pender, Alexandra; Wong, Selina K; Zhu, Jingyao; Ho, Cheryl; Ionescu, Diana N; Zhou, Chen
Abstract : Aims: Accurate assessment of programmed death‐ligand 1 (PD‐L1) levels in non‐small cell lung carcinoma (NSCLC) samples is complicated by intratumoral heterogeneity. We aimed to: (i) establish whether intratumoral PD‐L1 variation is associated with differences in local histotype; (ii) identify histotypes associated with a tendency for there to be higher or lower PD‐L1 scores; and (iii) estimate the frequency of clinically significant discordance in PD‐L1 levels between intratumoral histotype areas. Methods and results: We reviewed 166 NSCLC resection specimens clinically tested for PD‐L1 with the 22C3 pharmDx assay. Multiple histotypes were present in 55% (68/123) of non‐mucinous adenocarcinoma samples. Solid histotypes had significantly higher PD‐L1 levels than other histotypes, both when samples were grouped by predominant histotype, and when histotype areas within a tumour were compared ( P < 0.02). Lepidic areas had significantly lower PD‐L1 levels than other histotype areas within the same tumour ( P < 0.02). Discordance between intratumoral histotype areas at a clinically relevant threshold (PD‐L1 tumour proportion score of 1% or 50%) was present in 32% (22/68) of non‐mucinous adenocarcinoma specimens with multiple histotype areas. The lepidic histotype was most frequently involved in discordance. Conclusions: Intratumoral heterogeneity in PD‐L1 is associated with variation in histotype. Over‐representation of solid areas may increase the PD‐L1 score assigned to a tumour, whereas over‐representation of lepidic areas may decrease the PD‐L1 score. Evaluation of how histotype representation impacts on the predictive value of PD‐L1 testing is warranted.